Impact of Hull Breadth Modification on Tugboat Resistance: A Comparative Analysis Using Holtrop and CFD Methods - As’ad, Miftachus Surur; Pawara, Muhammad Uswah; Ikhwani, Rodlian Jamal; Wulandari, Amalia Ika (Indonesian Journal of Maritime Technology, 2024)
Estimating resistance experienced by a ship is crucial for determining the required engine power and fuel consumption to maintain a required speed. This study examines the comparative effects of altering the breadth of a tugboat from the approved initial design of 9 meters to a modified design of 8.6 meters, both utilizing the same engine power of 2x1018 HP. The analysis employs the Holtrop method, and Computational Fluid Dynamics (CFD). Using the Holtrop method, the largest differences at a speed of 14 knots were found to be 11.577 kN in resistance, 198.66 HP in engine power, and 0.617 g/kW.h in Specific Fuel Oil Consumption (SFOC), corresponding to a 5.141% difference in engine load. CFD results indicated the largest differences at 10 knots, with 9.009 kN in resistance, 102.47 HP in engine power, and 3.192 g/kW.h in SFOC, translating to a 5.034% difference in engine load. The modification of the breadth by 0.4 meters, while keeping the engine constant, impacts the resistance, engine power, and fuel consumption of the vessels.